Executive function performance in Chinese youth ice hockey players: a comparison between expert and novice groups - Wang, J.; Yang, X.; Shi, P. (Frontiers in Psychology, 2026)
Objective: This study aims to explore the executive function advantages of Chinese youth ice hockey players and provide a theoretical basis for the selection and training of ice hockey players. Methods: A total of 132 youth ice hockey players were recruited and divided into an expert group (65 players, mean age 15.8 years, mean training duration 6.7 years) and a novice group (67 players, mean age 16.2 years, mean training duration 3.2 years). The Flanker task, 2-back task, and More-odd shifting task were used to measure inhibition, updating, and shifting functions, respectively. Statistical analyses were performed using the Mann-Whitney U test, independent-samples t-test and Pearson correlation analysis. Results: Athletes exhibit a speed-accuracy trade-off. The expert group showed significantly shorter response times than the novice group in the congruent condition (Z = -2.681, p = 0.007) and incongruent condition (Z = -1.998, p = 0.046) of the Flanker task, the 2-back task (Z = -2.378, p = 0.017), and the size-parity shifting condition of the More-odd shifting task (Z = -2.548, p = 0.011). However, there were no significant differences in accuracy between the two groups across all tasks. In addition, training duration was significantly negatively correlated with response times in executive function tasks (inhibition congruent condition: r = -0.450; inhibition incongruent condition: r = -0.267; updating task: r = -0.257; shifting task: r = -0.185; all p < 0.05). Conclusion: Youth ice hockey players in the expert group demonstrate more superior executive functions, and there is a significant negative correlation between training duration and response time in executive function tasks.